Programmed cell death protein 1 inhibitor treatment is associated with acute kidney injury and hypocalcemia: meta-analysis. Issue 1 (11th May 2018) - Manohar, Sandhya; Kompotiatis, Panagiotis; Thongprayoon, Charat; Cheungpasitporn, Wisit; Herrmann, Joerg; Herrmann, Sandra M
ABSTRACT: Background: The aim of this meta-analysis was to assess the risks and incidence of nephrotoxicity and electrolyte abnormalities in patients receiving programmed cell death protein 1 (PD-1) inhibitors. Methods: We conducted a meta-analysis of clinical trials that monitored electrolyte levels and kidney functions during treatment with nivolumab or pembrolizumab by searching MEDLINE, EMBASE and the Cochrane Database from inception through April 2017. Our protocol is registered with International Prospective Register of Systematic Reviews; no.CRD42017060579. Results: A total of 48 clinical trials with a total of 11 482 patients were included. The overall pooled risk ratios (RR) of all acute kidney injury (AKI) and all electrolyte abnormalities in patients treated with PD-1 inhibitors were 1.86 [95% confidence interval (CI) 0.95–3.64] and 1.67 (95% CI 0.89–3.12), respectively. Compared with non-nephrotoxic controls, the pooled RR of AKI in patients treated with PD-1 inhibitors was 4.19 (95% CI 1.57–11.18). Prespecified subgroup analyses demonstrated a significant association between PD-1 inhibitors and hypocalcemia with a pooled RR of 10.87 (95% CI 1.40–84.16). The pooled estimated incidence rates of AKI and hypocalcemia in patients treated with PD-1 inhibitors were 2.2% (95% CI 1.5–3.0%) and 1.0% (95% CI 0.6–1.8%), respectively. Among patients who developed AKI with PD-1 inhibitors, the pooled estimated rate of interstitial nephritis was 16.6% (95% CI 10.2–26.0%). Conclusions: Treatment with PD-1 inhibitors is associated with a higher risk of AKI compared with non-nephrotoxic agents. It will be important to characterize the AKI patients to better understand the etiology behind the event. In addition, treatment with PD-1 inhibitors is associated with an increased risk of hypocalcemia. This study highlights a rare but serious adverse event of anti-PD-1 antibodies and we recommend, in addition to electrolytes panel, routine calcium monitoring.